COMPOUNDING GASOLINE A-92 WITH ETHANOL CAVITATION - Бойченко, С. В.; Ланецький, В. Г.; Черняк, Л. М.; Радомська, М. М.; Кондакова, О. Г. (Science-based technologies, 2016)
The road transport emissions currently have growing influence on the environment of big cities. Among the toxic substances, emitted by vehicles, the most harmful are carbon, nitrogen and sulfur oxides, aldehydes, hydrocarbons, aerosols and heavy metals, possessing carcinogenic and mutagenic potential. Therefore, according to the directives of the European Union environmental requirements to the regulation of automobile emissions are of high importance. Improving performance and environmental properties of motor gasoline is performed with the help of different additives. In particular, ethanol is used as a fuel component. There are various technologies of gasoline compounding, but the most promising technology is compounding of the fuel with hydrodynamic cavitation, which provides a high level of homogeneity of the mixture, the absence of components separation and increased octane number. Therefore, the study of compounding efficiency of gasoline A-92 with ethanol in amounts of 5%, 10%, 20% was conducted.